2012
DOI: 10.1007/s10067-012-1963-y
|View full text |Cite
|
Sign up to set email alerts
|

Tc-99m diethylenetriamine pentaacetic acid (DTPA) renal function reserve estimation: is it a reliable predictive tool for assessment of preclinical renal involvement in scleroderma patients?

Abstract: Prognosis of systemic sclerosis (SSc) depends on internal organ involvement. We assessed the value of renal function reserve (RFR) for the detection of preclinical nephropathy in scleroderma. Thirty SSc patients with normal serum creatinine and 30 healthy controls were included. Medsger disease severity score, glomerular filtration rate (GFR), and microalbuminuria were measured. Tc-99m DTPA was utilized for GFR measurement at baseline and after oral protein overload (stimulated GFR). RFR was calculated as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
(45 reference statements)
1
3
0
Order By: Relevance
“…The 99 m-Tc-DTPA scintigraphy also showed 80% abnormality of RFR in 30 SSc patients without renal involvement and regardless creatinine clearance levels, thus leading to the possibility of diagnosing preclinical renal involvement also in case of normal serum creatinine (58). This is in line with previous results from Livi et al (59) who showed that RFR was significantly reduced in SSc patients, in particular if they already presented arterial hypertension and reduced basal GFR.…”
Section: Scintigraphy and Rfrsupporting
confidence: 79%
“…The 99 m-Tc-DTPA scintigraphy also showed 80% abnormality of RFR in 30 SSc patients without renal involvement and regardless creatinine clearance levels, thus leading to the possibility of diagnosing preclinical renal involvement also in case of normal serum creatinine (58). This is in line with previous results from Livi et al (59) who showed that RFR was significantly reduced in SSc patients, in particular if they already presented arterial hypertension and reduced basal GFR.…”
Section: Scintigraphy and Rfrsupporting
confidence: 79%
“…AH is commonly feared Ewa Wielosz, Magdalena Dryglewska, Anna Górak, Ewa Łyś, Maria Majdan in SSc because it often heralds renal impairment. Renal involvement is observed in 60-80% of patients with SSc, while clinically based kidney symptoms in 10-40% [7]. In the majority of cases, chronic renal involvement is found to develop slowly over the course of years, triggering moderate often clinically unapparent renal function loss in 50% of the affected patients [8].…”
Section: Introductionmentioning
confidence: 99%
“…The dominant component of SSc pathophysiology is vascular damage, which can occur early in the course of the disease and affect different internal organs mainly the lung, heart and kidney. Renal involvement is observed in 60-80% of patients with SSc, while clinically based kidney symptoms in 10-40% [ 1 , 2 ]. In the majority of cases, chronic renal involvement is found, which develops slowly over the years and leads to moderate renal function loss, often clinically unapparent, in 50% of the affected [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Renal involvement is observed in 60-80% of patients with SSc, while clinically based kidney symptoms in 10-40% [ 1 , 2 ]. In the majority of cases, chronic renal involvement is found, which develops slowly over the years and leads to moderate renal function loss, often clinically unapparent, in 50% of the affected [ 2 ]. Apart from chronic kidney disease (CKD) with slow deterioration of the glomerular filtration rate (GFR), the other forms of kidney involvement in SSc are: scleroderma renal crisis (SRC), which affects about 10% of SSc patients, normotensive SRC, microalbuminuria, proteinuria and rather rare vasculitis [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%